2021
DOI: 10.21037/qims-20-1291
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical characteristics associated with atherosclerotic disease in the basilar artery: a magnetic resonance vessel wall imaging study

Abstract: Background: Vascular geometry may play an important role in the development of atherosclerosis. This study aimed to investigate the relationships between the geometrical characteristics of basilar artery (BA) and the presence, burden, and distribution of BA plaques using magnetic resonance vessel wall imaging.Methods: Patients with cerebrovascular symptoms in the posterior circulation were recruited and underwent magnetic resonance imaging. The BA's geometrical characteristics, including actual length, straigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Recent studies have used BA vascular geometrical risk factors to explain the presence and location of plaques 16) . For example, high tortuosity was associated with atherosclerotic plaques in the middle cerebral artery 17) , BA 18) , and superficial femoral artery 19) . BA plaques were frequently distributed in the lateral walls in symptomatic patients 18) .…”
Section: Measurement Of Ba Plaque Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have used BA vascular geometrical risk factors to explain the presence and location of plaques 16) . For example, high tortuosity was associated with atherosclerotic plaques in the middle cerebral artery 17) , BA 18) , and superficial femoral artery 19) . BA plaques were frequently distributed in the lateral walls in symptomatic patients 18) .…”
Section: Measurement Of Ba Plaque Characteristicsmentioning
confidence: 99%
“…For example, high tortuosity was associated with atherosclerotic plaques in the middle cerebral artery 17) , BA 18) , and superficial femoral artery 19) . BA plaques were frequently distributed in the lateral walls in symptomatic patients 18) . Asymptomatic BA plaques were demonstrated in 9.5% of individuals who underwent HRMRI during a routine health check-up 16) .…”
Section: Measurement Of Ba Plaque Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of atherosclerotic plaques is associated with the risk of ischemic events. [5][6][7] For example, it is more likely that atherosclerotic plaques located near perforating orifices are symptomatic during stent placement and may have a "snow plowing" effect. 8 Several postmortem studies have demonstrated that basilar artery perforators typically originate from the lateral and dorsal walls of the segment, distal from the anterior-inferior cerebellar artery, possibly explaining the high rate of postoperative complications.…”
mentioning
confidence: 99%